2019
DOI: 10.1016/j.neo.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Mitotic Exit of Ovarian Cancer Cells by Pharmaceutical Inhibition of the Anaphase-Promoting Complex Reduces Chromosomal Instability

Abstract: Paclitaxel is a frontline drug for the treatment of epithelial ovarian cancer (EOC). However, following paclitaxel-platinum based chemotherapy, tumor recurrence occurs in most ovarian cancer patients. Chromosomal instability (CIN) is a hallmark of cancer and represents genetic variation fueling tumor adaptation to cytotoxic effects of anticancer drugs. In this study, our Kaplan-Meier analysis including 263 ovarian cancer patients (stages I/II) revealed that high Polo-like kinase (PLK) 1 expression correlates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…In addition, although it has not been completedly translated to clinical trials, a specific PLK1 inhibitor, onvansertib, has shown good tolerance and efficacy in combination therapy with decitabine for leukemia treatment [31]. High expression of PLK1 has been reported to link to poor prognosis in patients, and targeting inhibition of PLK1 in combination with paclitaxel and proTAME has shown potent effects on the reduction of chromosomal instability and the subsequent apoptosis of OC cells [32]. These results indicated that miR-545-mediated PLK1 downregulation has potentials in OC control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although it has not been completedly translated to clinical trials, a specific PLK1 inhibitor, onvansertib, has shown good tolerance and efficacy in combination therapy with decitabine for leukemia treatment [31]. High expression of PLK1 has been reported to link to poor prognosis in patients, and targeting inhibition of PLK1 in combination with paclitaxel and proTAME has shown potent effects on the reduction of chromosomal instability and the subsequent apoptosis of OC cells [32]. These results indicated that miR-545-mediated PLK1 downregulation has potentials in OC control.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of proTAME on APC/C activity also seems to have great therapeutic potential. In combination with other inhibitors, proTAME was shown to be efficient in overcoming resistance caused by the hyperphosphorylation of CDH1 in glioblastoma cells [9], polo-like kinase 1 (PLK1)-based drug resistance in ovarian cancer cells [10] and CDC20-based resistance in diffuse large B-cell lymphoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…"Sustaining proliferative signaling" is a hallmark in cancer, but it might play a more dominant role in early-stages of OC than in late stages, where "activation of invasion/metastasis" or "resistance to cell death" take over in the overall clinical picture of OC. In the light of those thoughts, Ki-67 and Plk1 as targets for OC (55)(56)(57) come in consideration for early-stage OC in addition to their roles as diagnostic markers. Ki-67 is currently being tested in preclinical trials and small molecule inhibitors of Plk1 have received break-through designation by the FDA for clinical trials.…”
Section: Discussionmentioning
confidence: 99%